Graham Swift, Mothering Sunday. A Romance (London, Scribner, 2016, 149 pp. ISBN 9781471155246) Graham Swift, Un giorno di festa. Una storia d’amore. (Vicenza, Neri Pozza, 2016, 144 pp. ISBN 9788854513891) (Altre Modernità, 2018)
Graham Swift, Mothering Sunday. A Romance (London, Scribner, 2016, 149 pp. ISBN 9781471155246)Graham Swift, Un giorno di festa. Una storia d’amore. (Vicenza, Neri Pozza, 2016, 144 pp. ISBN 9788854513891)di Ilaria Villa